2020
DOI: 10.4236/jcc.2020.811008
|View full text |Cite
|
Sign up to set email alerts
|

A Short-Term PV Power Forecasting Method Using a Hybrid Kmeans-GRA-SVR Model under Ideal Weather Condition

Abstract: With the continuous increase of solar penetration rate, it has brought challenges to the smooth operation of the power grid. Therefore, to make photovoltaic power generation not affect the smooth operation of the grid, accurate photovoltaic power prediction is required. And short-term forecasting is essential for the deployment of daily power generation plans. In this paper, A short-term photovoltaic power generation forecast method based on K-means++, grey relational analysis (GRA) and support vector regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Lin et al faced the short-term PV power prediction problem and proposed a hybrid model based on the SVR model. The model could make more accurate predictions under ideal weather conditions through experimental analysis [8].…”
Section: Related Workmentioning
confidence: 99%
“…Lin et al faced the short-term PV power prediction problem and proposed a hybrid model based on the SVR model. The model could make more accurate predictions under ideal weather conditions through experimental analysis [8].…”
Section: Related Workmentioning
confidence: 99%
“…The support vector machine prediction algorithm is trained by the data from similarity day. The experiment showed that the behavior of the algorithm was better than the single support vector machine [3]. Zhang et al established a PV power forecasting method on account of a fuzzy support vector machine that was simple and easy to understand, and the PV power generation was predicted with the prediction model [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is done to get a more optimal prediction model [7]. One of them is using Hybrid K-means grey Relational Analysis and Support Vector Regression to predict short-term PV power [8]. The results obtained an accurate PV power prediction model with RMSE 0.9608.…”
Section: Introductionmentioning
confidence: 99%